Unplanned urbanization and hill cutting: a study on environmental change in sylhet - Rahman, Md. Habibur (BRAC University, 2012)
Bangladesh is a developing country having diversified environmental issues especially in the city area. The present study was conducted in Sylhet City Corporation; one of the rapidly developing urban areas in the north-eastern region of Bangladesh to identify the main environmental problems due to rapidly increase population, unplanned urbanization and hill cutting. The major environmental problems in the city are traffic obstruction, inappropriate solid waste disposal system, inadequate water supply, water logging state, hill cutting, chance of seismicity, etc. The nature and life style of Sylhet intimately related with the hills are thus under the threat of a drastic imbalance in its ecosystem. This study also investigates the causes of hill cutting along with its probable impact on environment such as deforestation, loss of biodiversity, ecological imbalance and climatic change, chances of earthquake will increase, destroying natural beauty, soil erosion and landslide, etc. Sylhet is located in highly seismic risk zone 3 but most of the buildings and apartments are constructed without considering earthquake risk. The City Corporation authority should take a new approach to tackle urban problems by investing new ways to solve them, taking advantages of unused resources and opportunities.